Three new species of Besleria (Gesneriaceae) from the southeastern Brazilian atlantic rainforest - Ferreira, Gabriel Emiliano; Costa, Idimá G.; Araújo, Andréa Onofre; Hopkins, Michael John Gilbert; Chautems, Alain (Phytotaxa, 2016)
Besleria is a Neotropical genus of terrestrial herbs, shrubs and small trees growing in the understory of rainforests, with more than 160 recognized species, and is one of the larger and more diverse genera of Gesneriaceae. It belongs to the monophyletic tribe Beslerieae, and recent phylogenetic studies indicate that the genus is monophyletic. During field expeditions in the Brazilian Atlantic Rainforest, we collected specimens that could not be identified as any described species. After morphological analysis and comparison with related species, we assigned these specimens to three new species of Besleria. In this paper, we describe and illustrate Besleria aurea, B. brevicalyx and B. diabolica and provide data on their ecology, distribution and conservation status. © 2016 Magnolia Press.